Changes in working conditions and physical health functioning among midlife and ageing employees - Mänty, Minna; Kouvonen, Anne; Lallukka, Tea; Lahti, Jouni; Lahelma, Eero; Rahkonen, Ossi (Scandinavian Journal of Work, Environment & Health, 2015)
' ' OBJECTIVES ': 'The aim this study was to examine the effect of changes in physical and psychosocial working conditions on physical health functioning among ageing municipal employees. ' ' METHODS ': 'Follow-up survey data were collected from midlife employees of the City of Helsinki, Finland, at three time points: wave 1 (2000–2002), wave 2 (2007), and wave 3 (2012). Changes in physical and psychosocial working conditions were assessed between waves 1 and 2. Physical health functioning was measured by the physical component summary (PCS) of the Short-Form 36 questionnaire at each of the three waves. In total, 2784 respondents (83% women) who remained employed over the follow-up were available for the analyses. Linear mixed-effect models were used to assess the associations and adjust for key covariates (age, gender, obesity, chronic diseases, and health behaviors). ' ' RESULTS ': 'Repeated and increased exposure to adverse physical working conditions was associated with greater decline in physical health functioning over time. In contrast, decrease in exposures reduced the decline. Of the psychosocial working conditions, changes in job demands had no effects on physical health functioning. However, decreased job control was associated with greater decline and repeated high or increased job control reduced the decline in physical health functioning over time. ' ' CONCLUSIONS ': 'Adverse changes in physical working conditions and job control were associated with greater decline in physical health functioning over time, whereas favorable changes in these exposures reduced the decline. Preventing deterioration and promoting improvement of working conditions are likely to help maintain better physical health functioning among ageing employees.
Keywords: ageing; ageing employee; follow-up; midlife; physical health; physical health functioning; physical working condition; psychosocial working condition; SF-36; working condition